Mechanistically informed non-invasive peripheral nerve stimulation for peripheral neuropathic pain: a randomised double-blind sham-controlled trial - Johnson, Selina; Marshall, Anne; Hughes, Dyfrig; Holmes, Emily; Henrich, Florian; Nurmikko, Turo; Sharma, Manohar; Frank, Bernhard; Bassett, Paul; Marshall, Andrew; Magerl, Walter; Goebel, Andreas (Journal of translational medicine, 2021)
Induction of long-term synaptic depression (LTD) is proposed as a treatment mechanism for chronic pain but remains untested in clinical populations. Two interlinked studies; (1) A patient-assessor blinded, randomised, sham-controlled clinical trial and (2) an open-label mechanistic study, sought to examine therapeutic LTD for persons with chronic peripheral nerve injury pain. (1) Patients were randomised using a concealed, computer-generated schedule to either active or sham non-invasive low-frequency nerve stimulation (LFS), for 3 months (minimum 10 min/day). The primary outcome was average pain intensity (0-10 Likert scale) recorded over 1 week, at 3 months, compared between study groups. (2) On trial completion, consenting subjects entered a mechanistic study assessing somatosensory changes in response to LFS. (1) 76 patients were randomised (38 per group), with 65 (31 active, 34 sham) included in the intention to treat analysis. The primary outcome was not significant, pain scores were 0.3 units lower in active group (95% CI − 1.0, 0.3; p = 0.30) giving an effect size of 0.19 (Cohen’s D). Two non-device related serious adverse events were reported. (2) In the mechanistic study (n = 19) primary outcomes of mechanical pain sensitivity (p = 0.006) and dynamic mechanical allodynia (p = 0.043) significantly improved indicating reduced mechanical hyperalgesia. Results from the RCT failed to reach significance. Results from the mechanistic study provide new evidence for effective induction of LTD in a clinical population. Taken together results add to mechanistic understanding of LTD and help inform future study design and approaches to treatment. Trial registration ISRCTN53432663.
Gesehen am 10.04.2024